STRATEGI PENGEMBANGAN PANTAI SEBAGAI DESTINASI EKOWISATA - Sarjono (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2022)
The aim of this reseach was to find the right strategy to develop the beach of Sipelot by taking into account the potential of tourism supply and demand. This research uses descriptive qualitative method, with observation, interviews, questionnaires as instruments for collecting data and analyzing data using SWOT. The results of the IFAS and EFAS analysis the Sipelot ecotourism coastal in quadrant I, which means growth strategy, meaning that Sipelot beach ecotourism will provide benefits if developed sustainably. Based on the SWOT matrix analysis, the strategy formulation to develop Sipelot beach ecotourism is 1. tourism product development strategy, 2. marketing and promotion strategy, 3. accessibility development strategy, 4. development strategy and improvement of public facilities and 5. business development strategies.